PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW II DENGAN MODIFIKASI PICTURE AND PICTURE TERHADAP KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR BIOLOGI PESERTA DIDIK KELAS XI MIA SMA PGRI 4 DENPASAR TAHUN PELAJARAN 2016/2017 - A.A. Istri Mirah Dharmadewi; Ni Wayan Eli Suwarmayanti (Widyadari : Jurnal Pendidikan, 2020)
This research aims to know the influence of cooperative learning model jigsaw type II with modifications to the Picture and picture against the ability of the creative thinking and learning outcomes learner class XI biology MIA SMA PGRI 4 Denpasar. The type of research is quasi ekseriment. The population in the study were students of class XI MIA SMA PGRI 4 Denpasar consisting of three classes, involving samples of 85 students taken with multistage sampling technique. Independent variable in this research is cooperative learning model of jigsaw II type with picture and picture modification, while creative thinking ability and biology learning result as dependent variable. Biology learning result data was collected by biology test result and creative thinking ability data was collected by questionnaire of creative thinking ability. Data analysis using t-test and MANOVA with the help of SPSS 16.0 for windowsBased on the findings, it can be concluded that: (1). There is a significant influence of cooperative learning model type jigsaw II with the modification of picture and picture to the creative thinking ability of students XI MIA SMA PGRI 4 Denpasar with sig value. ≤ α (0,000 <0,05), (2). There is a significant influence from cooperative learning model type jigsaw II with the modification of picture and picture to result of biology learners learner XI MIA SMA PGRI 4 Denpasar with sig value. ≤ α (0,000 <0,05), and (3). There is significant influence from jigsaw II type cooperative learning model with picture and picture modification to creative thinking ability and biology learning result of XI MIA students SMA PGRI 4 Denpasar simultaneously with Sig value. ≤ α (0,000 <0.05).